Economic Contribution of Homestay Tourism: A Case Study of Magar Homestay of Naruwal, Lamjung - Magar, Dambar Ale (Marsyangdi Journal, 2021)
Tourism involving homestay is one of the Nepal government’s key efforts to diversify its cultural tourism product. Moreover, homestay can be a new model of tourism development in Nepal. This article aims to highlight the economic contribution of homestay entities based on the descriptive design. Data were collected from the ten homestay entities of Magar homestay at Naruwal, Lamjung through in-depth interviews. The contribution of homestays has been studied from various aspects like average income earned, the number of jobs created, women entrepreneurs, reverse migration, development of infrastructure, rise in living standard, etc. The result shows that the rate of income and expenditure has been gradually increased since the date of homestay tourism commencement in the community. This study has found that many of the respondents have managed their daily expenditures through the income of homestay entities. All homestay operators have reported the increment in their economic status. However, it is also found that there is a need to improve the quality of service to increase the flow of national and international visitors/tourists.